THE EPISTEMOLOGY OF PRACTICE IN TEACHER EDUCATION: CONSIDERATIONS ON THE DIVERSITY OF ITS PERSPECTIVES AND OF ITS COORDINATIONS - Oliveira, R. G. [UNESP] (Centro Federal Educacao Tecnologica Rio Grande Norte, 2021)
This article is a theoretical essay that presents reflections, actions and questions that can be considered in the constitution of epistemological perspectives for teacher education from epistemology of practice. It is understood that the complexity and potential of the coordination of concepts from different explanations, as well as its limits of approximation, can contribute to the constitution of these perspectives. Among these concepts are, for example, the concepts of reflective and investigative teacher, as well as situated learning in context and also the teacher professionalization.
Keywords: Epistemology of practice; teacher knowledge; teacher education; teacher profissionalization